KIR training and use of simple science teaching aids for increase understanding and motivation teachers and students of MTs YKUI Maskumabang - Munasir, Munasir; Hariyono, Eko; Dwikoranto, Dwikoranto; Kusumawati, Diah Hari; Saputra, Oka; F, Fitriana (Journal of Dedication in Community, 2023)
Not all school active in follow race because lack of understanding and motivation. Based on the problem that needs to be done to increase motivation and understanding partner. The study objective is to increase the understanding and motivation of partners. To follow race until the national level. The method used is to give test understanding, and subsequent questionnaires will analyzed to see the extent of influence PKM has implemented. The location of PKM activities is at MTs YKUI Maskumambang Gresik Regency. Based on data analysis, a percentage of 98.00% can be obtained to increase understanding, 95.33% can motivate partners, and 90% agree that the PKM program is implemented very useful.